A year down yonder - Peck, Richard, 1934- (New York : Dial Books for Young Readers, 2000)
In 1937, during the Depression, fifteen-year-old Mary Alice, initially apprehensive about leaving Chicago to spend a year with her fearsome, larger-than-life grandmother in rural Illinois, gradually begins to better understand and admire her grandmother's unusual qualities.
It was within the pages of Richard Peck's Newbery Honor-winning A Long Way from Chicago that Mary Alice and Grandma Dowdel first made their captivating debut.
Newbery Medal, 2001
Keywords: Grandmothers -- Fiction; Depressions -- 1929 -- Fiction; Country life -- Illinois -- Fiction; Illinois -- Fiction